2010
DOI: 10.1038/icb.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and protective efficacy of mycobacterial DNA vaccines incorporating plasmid‐encoded cytokines against Mycobacterium bovis

Abstract: DNA-based vaccines, alone or in combination with other sub-unit vaccination regimes, represent an alternative to live mycobacterial vaccines for protective immunization against tuberculosis. Here, we have used a murine immunization or Mycobacteriam bovis aerosol challenge model to assess the immunogenicity and protective efficacy of mycobacterial DNA vaccines. Mice that received immunization with DNA constructs encoding M. bovis antigen 85A (Ag85-A) and arget(ESAT-6) produced measurable interferon-gamma (IFN-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To increase the immunoreaction of single gene and antigen, many scholars have evolved immunity investigation on fusion genes and proteins. Ag85A/ESAT6 DNA vaccines-MVA enhanced the resistance anti-M. bovis aerosol [10]. Mouse vaccinated with Ag85A-ESAT-6 polyester beads packaged by E. coli and Lactococcus lactis produced high-level IgG, INF-γ, IL-2, IL-6,TNF-α and IL-17a in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the immunoreaction of single gene and antigen, many scholars have evolved immunity investigation on fusion genes and proteins. Ag85A/ESAT6 DNA vaccines-MVA enhanced the resistance anti-M. bovis aerosol [10]. Mouse vaccinated with Ag85A-ESAT-6 polyester beads packaged by E. coli and Lactococcus lactis produced high-level IgG, INF-γ, IL-2, IL-6,TNF-α and IL-17a in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…M.bovis fusion vaccines of mpb64,ag85b and esat-6 can stimulate mouse produce high level antibody, lymphocyte, INF-γ and IL-2, and the protective result reached the immunoprotection level of BCG [14]. C57BL/6 mice was vaccinated with recombinant BCG(constructed with Ag85B-Rv3425 and Ag85B-MPT64-Mbt8.4 respectively), the results indicated that the level of antigen-stimulated T cells expressing IFN-γ and antibody titer were significantly higher than that of BCG [15,16], the level of IFN-γ demonstrated notable difference, rBCG has preferably immunoprotection [16].Ag85A/ESAT6 DNA vaccines -MVA enhanced the resistance anti-M. bovis aerosol [17]. Recombinant fusion protein…”
Section: Discussionmentioning
confidence: 99%
“…But significant differences in spleen bacterial counts were observed between those receiving PHB beads and BCG and PBS. Young, et al [26] used murine immunization and M. bovis aerosol challenge model to assess the immunogenicity and protective efficacy of mycobacterial DNA vaccines Ag85A/ESAT6.The results demonstrated that Ag85A/ESAT6 DNA vaccines-MVA enhanced the resistance anti-M. bovis aerosol. Abel, et al [27] and Hoft, et al [28] investigated the safety and immunogenicity in healthy M. tuberculosis-uninfected BCG-vaccinated adults from a tuberculosis-endemic region of South Africa and USA, the results confirmed that recombinant fusion protein Ag85A-Ag85B-TB10.4 can stimulate strongly CD 4 + T cells reaction and persistant CD 8 + T cells reaction, and is a promising vaccine.…”
Section: Methodsmentioning
confidence: 99%